Microbiota activation and regulation of adaptive immunity - Heidari, Mozhdeh; Maleki Vareki, Saman; Yaghobi, Ramin; Karimi, Mohammad Hossein (Frontiers in Immunology, 2024)
In the mucosa, T cells and B cells of the immune system are essential for maintaining immune homeostasis by suppressing reactions to harmless antigens and upholding the integrity of intestinal mucosal barrier functions. Host immunity and homeostasis are regulated by metabolites produced by the gut microbiota, which has developed through the long-term coevolution of the host and the gut biome. This is achieved by the immunological system's tolerance for symbiote microbiota, and its ability to generate a proinflammatory response against invasive organisms. The imbalance of the intestinal immune system with commensal organisms is causing a disturbance in the homeostasis of the gut microbiome. The lack of balance results in microbiota dysbiosis, the weakened integrity of the gut barrier, and the development of inflammatory immune reactions toward symbiotic organisms. Researchers may uncover potential therapeutic targets for preventing or regulating inflammatory diseases by understanding the interactions between adaptive immunity and the microbiota. This discussion will explore the connection between adaptive immunity and microbiota.